How occupational therapists are incorporating information and communication technology into intervention with older adults: A scoping review. - Hibler, Victoria; Martinson, Ellen; Rice, Emma; Tucker, Jamie; Fortuna, Jennifer; Cantwell-Jurkovic, Laureen (Assistive Technology, 2025)
Use of information and communication technology (ICT) (computers and smartphones) during everyday occupations is growing as rapidly as the older adult population. ICT is incorporated into occupational therapy (OT) interventions to improve performance in everyday activities. Limited competence in ICT can jeopardize wellness, autonomy, and contribute to isolation. This scoping review explores how ICT is incorporated into OT interventions and identifies knowledge gaps in the literature. Five databases were searched using a scoping review methodological framework. The included articles were peer-reviewed, written in English, focused on ICT in OT practice and include participants 65 and older. The results were summarized and reported with descriptive statistics and qualitative analysis. Twenty-three articles met the inclusion criteria. Findings include differences in participant characteristics, ICT devices, and outcome measures. Common themes identified benefits and barriers to ICT training, education, and occupational performance. Gaps in the literature include guidelines for intervention and the impact of specific health conditions on ICT performance. When incorporating ICT into OT interventions, consideration must be given to age-related deficits, perceptions of technology, and access to devices. Additional research is needed to establish evidence-based guidelines for OT interventions that incorporate ICT-mediated occupations with older adults.